2023
DOI: 10.3390/plants12152871
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Phytochemical and Biological Evaluation of Rudbeckia hirta Flowers

Abstract: Black-eyed Susan (Rudbeckia hirta L.), a flowering plant with various traditional medicinal uses, has recently garnered interest for its therapeutic properties. However, little is known about the potential therapeutic activities of the plant species. The current study focused on conducting a comprehensive investigation into the chemical composition and bioactivity of black-eyed Susan cultivated in Romania. Untargeted metabolite profiling and UHPLC-HR-MS phytochemical analysis of the studied extract revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 86 publications
(104 reference statements)
0
2
0
Order By: Relevance
“…Through analysis of the chemical constituents of RHE, we found that RHE contains 22 compounds, ten of which were avone or avonoid derivatives, accounting for 75.47% of the total compound contents. The extracts of R. hirta have revealed the presence of more than 250 compounds, including sesquiterpene lactones, polyphenolic acids, avonoids, amino acids, and fatty acids (Burlec et al, 2023). We believe that the insecticidal activity of RHE was mainly attributed to the avone and avonoid derivatives.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Through analysis of the chemical constituents of RHE, we found that RHE contains 22 compounds, ten of which were avone or avonoid derivatives, accounting for 75.47% of the total compound contents. The extracts of R. hirta have revealed the presence of more than 250 compounds, including sesquiterpene lactones, polyphenolic acids, avonoids, amino acids, and fatty acids (Burlec et al, 2023). We believe that the insecticidal activity of RHE was mainly attributed to the avone and avonoid derivatives.…”
Section: Discussionmentioning
confidence: 91%
“…This plant has been used to treat fevers, colds, and headaches, and was believed to have anti-in ammatory and analgesic properties (Michael et al, 2014). R. hirta was also thought to have antimicrobial properties (Burlec et al, 2023;Setzer 2018). The ethanol extracts of R. hirta were shown to exert repellent effects against the Popillia japonica (Metzger et al, 1932).…”
Section: Introductionmentioning
confidence: 99%